Assessing the Effects of High Sugar and Protein Diets on Reproduction and Longevity in Crickets - Amjad, Sohaib; Rollo, David C.. (The Meducator, 2012)
Studies on longevity are becoming increasingly important due to the aging population. The house cricket, Acheta domesticus, is an effective model for longevity studies due to its short lifespan of 120 days. This study explored the effects of diet on reproduction and longevity in A. domesticus. There were four treatment groups: 1) control diet with reproduction, 2) control diet with reproductive isolation, 3) high protein diet with reproduction, and 4) high sugar diet with reproduction. We began monitoring the crickets following maturity to allow for reproductive analysis. Death counts were conducted daily, followed by replenishment of food and water supplies. Egg counts and weight measurements were conducted weekly. Results showed that crickets on the high sugar diet had significantly longer lifespan than other treatments. The lowest lifespan was seen in crickets on the high protein diet. Conversely, the highest reproductive output was seen in the high protein diet and the lowest was in the high sugar diet. The reproductively isolated control group had a significantly greater longevity than the reproductive control group. Taken together, the research shows an inverse relationship between reproduction and longevity as modulated by dietary consumption of proteins and carbohydrates.